Велика Акаржа та періодизація пам’яток середнього етапу пізнього палеоліту азово-причорноморських степів - Сапожников, І.В. (Археологія, 2002)
На основі детального аналізу геологічних і палінологічних матеріалів, а також ізотопних дат розглянуто проблеми датування пам'яток середнього етапу пізнього палеоліту степової зони Північного Причорномор’я і Приазов‘я. Запропоновано періодизацію цього етапу, уточнену і обґрунтовану на базі стратиграфічної схеми М.Ф. Веклича. В статье рассмотрены проблемы датирования наиболее значимых памятников среднего этапа позднего палеолита зоны степей Северного Причерноморья и Приазовья, которые в целом соотносятся с раннепричерноморским подгоризонтом причерноморского горизонта лессовой формации Украины, на базе детального анализа геологических и палинологических материалов, а также существующих изотопных дат. Предложена уточненная и обоснованная периодизация данного этапа, разработанная на базе стратиграфической схемы Веклича.
Автор предложил разделить раннепричерноморский подгоризонт на два уровня. Первый из них совпадает с начальной фазой валдайского оледенения и датируется 22—21 тысячелетиями до наших дней (нижний слой Сагайдака I, Анетовка I, Золотовка I, Мураловка). Второй уровень сопоставлен с максимальной фазой оледенения и датируется 20—19 тысячелетиями ВР (большая Аккаржа, Амвросиевка, Анетовка II, верхний слой Вороны-3 и, возможно, Ямы). Допускается существование еще одного, третьего, уровня, который может быть связан с заключительной фазой последнего оледенения и датироваться от 18 до 17— 16,5 тыс. лет ВР. The problems of dating the most significant sites of the middle stage of the late Paleolithic in the Steppe, Black Sea, and Azov areas are considered in the article. These sites correlate with the early Black Sea subhorizon (pc) of the Black Sea horizon of the loess formation of Ukraine, based on the detailed analysis of geological and palinological materials and also on the existing radioactive izotype dating. The improved and grounded periodization of this phase worked out based on M.F. Veklich’s stratigraphic scheme, has been suggested here.
The author proposed to divide the Early Black Sea horizon into two levels. The first one coincides with the starting phase of Valdaj glacial and is dated to the 22nd–21st millennia BP (the lower layer of Sagaidak I, Anetovka I, Zolotovka I, Muralovka). The second level correlates with the maximal phase of glacial and is dated to the 20th–19th millennia BP (Bolshaya Akkarzha, Amvrosievka, Anetovka II, the upper layer of Voroni 3, and perhaps Jamy). The author also assumes the existence of another, the third level, which may be connected with the final phase of the last glacial and may be dated from 18 up to 17–16.5 thousand years ago.